Deciphering the Reactivity of Quinoxaline - Dam, Binoyargha; Das, Bubul; Patel, Bhisma K. (Synlett, 2025)
This personal account is primarily focused on various functionalization tools for the quinoxaline moiety. This bicyclic heterocycle is widespread in natural products, pharmaceutical drugs, and agrochemicals and is also one of the core motifs for material science applications. Transition metals can induce various reactivity in this benzopyrazine ring viz., C3–H functionalization, annulation, spirocyclization, and bis-functionalization across the C=N bond, and so forth. Such functionalization enhances the biological activity of the core, thereby underscoring the importance of various synthetic processes. Our group has been actively engaged in developing new sustainable synthetic approaches for the functionalization of quinoxaline using thermal or green energy in the form of visible-light or solar energy. This review summarizes the various synthetic methodologies developed in our laboratory in order to functionalize the quinoxaline moiety.
Keywords: Quinoxaline; C–H functionalization; C3 maleimidation; Spiro-cyclization dehydrogenation; Bis-Functionalization; Oxidative annulations; Quaternary hydroxylation; Spiro-etherification